Negative affect mediates the association between negative news exposure and eye-tracking measures of attentional bias to food and alcohol cues among college students - John Brand; Catherine Stanger; Caroline Borowy; Elizabeth Shelto; Delaina Carlson; Min-Jeong Yang; Diane Gilbert-Diamond (PLoS ONE, 2026)
Objective To test the novel hypothesis that negative news exposure may lead to an increase in negative affect, which in turn leads to an increase in the amount of attention given to food and alcohol cues. Method Forty-two college students made two laboratory visits, approximately 1-week apart. During each visit, students watched 15 minutes of short news clips while having their eye movements monitored. Participants were randomized to view either negative or control news during their first visit and watched the other news condition during their second visit. Food, alcohol, and control commercials were randomly shown between each news clip. At the end of each commercial, a static image of the branded food, alcohol, or control product appeared in middle of the screen and stayed visible for 5 seconds. We recorded two robust measures of attentional bias to the static image: first fixation bias and cumulative fixation bias. The Maastricht Momentary Mood Questionnaire (3MQ) was completed prior to the news clips being shown to record a baseline level of negative affect. Participants completed the 3MQ again following viewing the news clips to measure changes in negative affect. Results In a series of linear regressions, we found that, overall, viewing negative news was associated with a statistically significant increase in negative affect (β = 0.72, P < 0.001), as well as a statistically significant increase in cumulative fixation bias (P = 0.041) and a nonsignificant increase in first fixation bias (P = 0.074) to food and alcohol vs. control cues. Furthermore, our data suggests that negative affect may partially mediate the association between negative news exposure and cumulative fixation bias, though the mediation effect did not reach statistical significance (β = 0.14; P = 0.056). Conclusion In conclusion, exposure to negative news media increased negative affect and attentional bias to food and alcohol cues among college students, suggesting that distressing media may contribute to maladaptive coping behaviors such as emotional eating and alcohol use.